Conjugated Linoleic Acid Accumulation via 10-Hydroxy-12-Octadecaenoic Acid during Microaerobic Transformation of Linoleic Acid by Lactobacillus acidophilus - Ogawa, Jun (American Society for Microbiology, 2001)
Specific isomers of conjugated linoleic acid (CLA), a fatty acid with potentially beneficial physiological and anticarcinogenic effects, were efficiently produced from linoleic acid by washed cells of Lactobacillus acidophilus AKU 1137 under microaerobic conditions, and the metabolic pathway of CLA production from linoleic acid is explained for the first time. The CLA isomers produced were identified as cis-9, trans-11- or trans-9, cis-11-octadecadienoic acid and trans-9, trans-11-octadecadienoic acid. Preceding the production of CLA, hydroxy fatty acids identified as 10-hydroxy-cis-12-octadecaenoic acid and 10-hydroxy-trans-12-octadecaenoic acid had accumulated. The isolated 10-hydroxy-cis-12-octadecaenoic acid was transformed into CLA during incubation with washed cells of L. acidophilus, suggesting that this hydroxy fatty acid is one of the intermediates of CLA production from linoleic acid. The washed cells of L. acidophilus producing high levels of CLA were obtained by cultivation in a medium containing linoleic acid, indicating that the enzyme system for CLA production is induced by linoleic acid. After 4 days of reaction with these washed cells, more than 95% of the added linoleic acid (5 mg/ml) was transformed into CLA, and the CLA content in total fatty acids recovered exceeded 80% (wt/wt). Almost all of the CLA produced was in the cells or was associated with the cells as free fatty acid.